2019
DOI: 10.1371/journal.pone.0225165
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of mortality among patients with drug-resistant tuberculosis in northern Nigeria

Abstract: BackgroundDrug-Resistant tuberculosis (DR-TB) is estimated to cause about 10% of all TB related deaths. There is dearth of data on determinants of DR-TB mortality in Nigeria. Death among DR-TB treated cohorts in Nigeria from 2010 to 2013 was 30%, 29%, 15% and 13% respectively. Our objective was to identify factors affecting survival among DR-TB patients in northern Nigeria.MethodsDemographic and clinical data of all DR-TB patients enrolled in Kano, Katsina and Bauchi states of Nigeria between 1st February 2015… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 16 publications
3
14
0
Order By: Relevance
“…Relatively lower mortality rates were reported from Kenya (Kiprotich et al, 2014), Sudan (Ali et al, 2019), Egypt (Gadallah et al, 2016), Brazil (Gayoso et al, 2018), USA (Kurbatova et al, 2012), Lativa (Leimane et al, 2005), Tanzania (Mollel and Chilongola, 2017), and China (Zhang et al, 2018). However, higher mortality reported from Pakistan (Kanwal et al, 2017), Nigeria (Bajehson et al, 2019), Eastern Europe (Balabanova et al, 2016), South Africa (Chingonzoh et al, 2018;Farley et al, 2011;Schnippel et al, 2015), Lesotho (Dheda et al, 2012), South Korea (Jeon et al, 2011), Bulgaria (Milanov et al, 2015) and Peru (Mitnick et al, 2013). The pooled incidence density rate of mortality in this study was 9.28/1000 PMs.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Relatively lower mortality rates were reported from Kenya (Kiprotich et al, 2014), Sudan (Ali et al, 2019), Egypt (Gadallah et al, 2016), Brazil (Gayoso et al, 2018), USA (Kurbatova et al, 2012), Lativa (Leimane et al, 2005), Tanzania (Mollel and Chilongola, 2017), and China (Zhang et al, 2018). However, higher mortality reported from Pakistan (Kanwal et al, 2017), Nigeria (Bajehson et al, 2019), Eastern Europe (Balabanova et al, 2016), South Africa (Chingonzoh et al, 2018;Farley et al, 2011;Schnippel et al, 2015), Lesotho (Dheda et al, 2012), South Korea (Jeon et al, 2011), Bulgaria (Milanov et al, 2015) and Peru (Mitnick et al, 2013). The pooled incidence density rate of mortality in this study was 9.28/1000 PMs.…”
Section: Discussionmentioning
confidence: 95%
“…Even though treatments of MDR-TB save the lives of millions globally, a significant proportion of patients are still dying or have a poor treatment outcome. It was reported elsewhere that the majority of deaths and poor treatment outcomes occur during the first months of the MDR-TB treatment course (Bajehson et al, 2019;Balabanova et al, 2016;Chingonzoh et al, 2018;Farley et al, 2011;Kanwal et al, 2017;Schnippel et al, 2015;Dheda et al, 2012;Jeon et al, 2011); individual studies conducted in Ethiopia also supported this (Ketema et al, 2019;Alene et al, 2017;Getachew et al, 2013;Girum et al, 2017;Shimbre et al, 2020;Gebre et al, 2020;Fantaw et al, 2018). However, there is no comprehensive report on the time to poor treatment outcome and its predictors among patients treated for MDR-TB in Ethiopia.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Similarly, the risk of death during treatment with second-line anti-tuberculosis drugs was significantly increased by 50% (1.50 times higher) among HIV-infected patients compared with those HIV-uninfected ones. Consistently, variable but positive relationships indicated between mortality during course of the second-line anti-tuberculosis regimen and presence of HIV-infection with 1.46 (in a study with 3,802 participants) [ 68 ]; 1.7 (for ART initiated) and 2.3 (for no ART) (in a study with 3,566 participants) [ 69 ]; 2.35 (in a study with 147 participants) [ 70 ]; 4.2 (in a study with 1,768 participants) [ 71 ]; 5.6 (in a study with 2,097 participants) [ 72 ]; 5.6 (in a study with 1,209 participants) [ 73 ]; and 29.9 (in a study with 50 participants) [ 74 ] times higher risks or odds of death in the HIV-infected patients than in those HIV-uninfected counterparts. Again, reports for the rates of mortality during the second-line TB therapy among HIV-infected versus HIV-uninfected patients showed 14% versus 6% in a study with 206 participants [ 75 ], 20% versus 9% in a study with 671 participants [ 76 ], and 72% versus 20% in a study with 173 participants [ 77 ]; all of them aligned with our study finding.…”
Section: Discussionmentioning
confidence: 88%
“…For example, in a meta-analysis, treatment delay was identified as a predictor of poor treatment outcome (death and failure) [ 13 ]. A study conducted by Bajehson et al found a significant negative association between treatment delay and survival [ 14 ]. One possible explanation for this is that delay is significantly associated with clinical severity at presentation [ 15 ].…”
Section: Introductionmentioning
confidence: 99%